Formação continuada de professores dos anos iniciais: - Barros, Leicijane da Silva (2023)
This research aims to identify and analyze the terminology of the domain of Continuing Education for Teachers in Elementary School ́s Early Years, through the presentation of a system of concepts of the terminological set studied, of a prototype of field glossary of this specialty, as well as the analysis of the main linguistic configurations that form the terminology of this area. The thesis is based on the theoretical assumptions of Lexicon Sciences (BARBOSA, 1996, 1999, 2005; BARROS, 2004; BIDERMAN, 2001, 2006; CABRÉ, 1993, 1998, 1999, 2002; FAULSTICH, 1995, 2006; KRIEGER; FINATTO, 2020) and Corpus Linguistics (BERBER SARDINHA, 2000, 2004; SÁNCHEZ, 1995; SINCLAIR; 1991). The methodological procedures were guided by the Communicative Theory of Terminology - CTT (CABRÉ, 1999) and Corpus Linguistics (BERBER SARDINHA, 2000, 2004). Two computational tools were used for corpus processing, extraction and analysis of terms: BootCaT and AntConc. A corpus consisting of 157 materials was used, including texts and official documents published by Ministry of Education (MEC), National Institute of Educational Studies and Research Anísio Teixeira (INEP) and Center for Literacy, Reading and Writing (Ceale), in addition to theses, dissertations and articles that deal with the subject under study. With the expert help in the field, 2,851 terms were validated, which were distributed into three subdomains to facilitate access by its consultants, namely: linguistic knowledge, mathematical knowledge and didactic educational knowledge. After identifying the terms of the specialty domain under study, we present a prototype of glossary of the area. The analyzes demonstrated that the terminological profile of the studied domain is formed, mostly, by complex terms, with a substantive base and that the suffix derivation was the most productive formation process in the constitution of the simple terms of terminological set analyzed. Loanwords also stand out, especially among discursive practices on web, due to the influence of technological advances and rapid dissemination in social networks, as well as a significant occurrence of abbreviation, with a predominance of acronyms. The relevance of this research lies in identifying the terminology of continuing education for teachers in early years, establishing possible boundaries with other similar areas, which we hope to contribute to the development of future studies. In addition, we hope that this investigation may serve as a reference for the elaboration of terminographical objects in this field of knowledge and, above all, that it may help the continuing education courses for teachers, with regard to access, even if a posteriori, to a product that will be able to subsidize the practice of trainers/study advisors and educators who work in early years, mostly pedagogues, whose effectiveness of the work developed is often compromised by lack of knowledge of specific terms and concepts in the area under study.